IMPLEMENTASI UPS (UNINTERUPPTIBLE POWER SUPPLY) SEBAGAI BACKUP DAYA CADANGAN DI PT. ASDP INDONESIA FERRY - Nuga Pratama; Bagus Dwi Cahyono (Pusat Riset dan Inovasi Nasional, 2022)
.Every company certainly has operating equipment that usually runs continuously and relies on electricity as an energy source whose distribution must be appropriate to be efficient in its use. Every company that has important activities that use electronic devices, of course, must have a power backup so that sudden power cuts do not occur, because if this happens frequently it will cause damage to electronic devices, one of which is using a UPS (Uninterruptible Power Supply). Uninterruptible Power Supply (UPS) is an electronic device capable of providing temporary backup power when the main power supply is cut off. This UPS is also an electronic device that can protect all types of electronic equipment that is vulnerable to current or voltage instability. The purpose of this study is to understand and know the working principle and how to maintain the use of UPS. The method used is the method of observation in the company to obtain research data. At PT. ASDP Indonesia Ferry uses two types of UPS which have different capacities, namely 0.8KVA and 3KVA to supply power to each electronic device that is used regularly. Of the two types of UPS, it can be used to back up electrical power when the main power source is suddenly cut off.